Living alone predicts non-home discharge post elective hip arthroplasty: A matched-pair cohort study - Benjamin K. Agnor; Ziyad O. Knio; Zhiyi Zuo (PLoS ONE, 2025)
The impact of home support and interaction with family members on recovery and perioperative outcomes remains unclear. We determined whether living alone was predictive of discharge disposition following total hip arthroplasty (THA). Data were from American College of Surgeons National Surgical Quality Improvement Program participating hospitals in 2021. The primary endpoint was discharging disposition. A total of 1716 patients living alone and 3961 with others at home were identified. The 1:1 propensity-matched cohort included 3248 total patients (1624 in each group). On univariate analysis, living alone was associated with non-home discharge (22.0% [358/1624] vs. 10.5% [170/1623]; odds ratio [OR], 2.42 [95% CI, 1.98 to 2.94]; P < .001), need for services in those returning home (63.1% [799/1266] vs. 57.7% [839/1453]; OR, 1.25 [95% CI, 1.07 to 1.46]; P = .004), and increased length of hospital stay (2.05 vs. 1.72 days; mean difference, 0.34 [95% CI, 0.18 to 0.49]; P < .001). On multivariable analysis, living alone remained an independent predictor of non-home discharge (adjusted odds ratio, 2.84 [95% CI, 2.30 to 3.54]; c = 0.734). Thus, compared to propensity-matched THA patients with others at home, those living alone experience a much greater rate of non-home discharge and need for support.